IL-4 subverts mycobacterial containment in Mycobacterium tuberculosis-infected human macrophages. Issue 2 (8th August 2019) - Pooran, Anil; Davids, Malika; Nel, Andrew; Shoko, Aubrey; Blackburn, Jonathan; Dheda, Keertan
Protective immunity against Mycobacterium tuberculosis is poorly understood. The role of interleukin (IL)-4, the archetypal T-helper type 2 (Th2) cytokine, in the immunopathogenesis of human tuberculosis remains unclear. Blood and/or bronchoalveolar lavage fluid (BAL) were obtained from participants with pulmonary tuberculosis (TB) (n=23) and presumed latent TB infection (LTBI) (n=22). Messenger RNA expression levels of interferon (IFN)-γ, IL-4 and its splice variant IL-4δ2 were determined by real-time PCR. The effect of human recombinant (hr)IL-4 on mycobacterial survival/containment (CFU·mL −1 ) was evaluated in M. tuberculosis- infected macrophages co-cultured with mycobacterial antigen-primed effector T-cells. Regulatory T-cell (Treg) and Th1 cytokine levels were evaluated using flow cytometry. In blood, but not BAL, IL-4 mRNA levels (p=0.02) and the IL-4/IFN-γ ratio (p=0.01) was higher in TB versus LTBI. hrIL-4 reduced mycobacterial containment in infected macrophages (p<0.008) in a dose-dependent manner and was associated with an increase in Tregs (p<0.001), but decreased CD4 + Th1 cytokine levels (CD4 + IFN-γ + p<0.001; CD4 + TNFα + p=0.01). Blocking IL-4 significantly neutralised mycobacterial containment (p=0.03), CD4 + IFNγ + levels (p=0.03) and Treg expression (p=0.03). IL-4 can subvert mycobacterial containment in human macrophages, probably via perturbations in Treg and Th1-linked pathways. These data may have implications for the design of effective TB vaccines and host-directed therapies. TB patients express high IL-4 levels and exhibit a compartment-specific skewed Th2/Th1 response. In vitro, IL-4 subverts mycobacterial containment in M. tuberculosis -infected human macrophages indicating its potential utility as an immunotherapeutic target. bit.ly/2HclAOH